TRANSFORMASI DIGITAL UNTUK UMKM: PELATIHAN KETERAMPILAN DESAIN POSTER SEBAGAI MEDIA PROMOSI UNTUK USAHA MIKRO DI BANDUNG BARAT - Nudiati, Deti; Krisnayanti, Krisnayanti; Rohma, Vinanti Julia; Nuraeni, Rini; Maesaroh, Tasbiah Siti (IKIP Siliwangi, 2025)
This study explores the effectiveness of a Canva-based digital poster design training in empowering micro, small, and medium-sized enterprises (MSMEs) in Kp. Pasir Handap, West Bandung. The training aimed to enhance participants’ technical skills, digital literacy, and confidence in using technology for promotional purposes. Employing a one-group pretest-posttest design, the study involved ten MSME participants with limited prior experience in graphic design. Quantitative data collected through pre- and post-training questionnaires revealed significant improvements in participants’ understanding and use of Canva’s basic features. The training also incorporated adult learning principles (andragogy) to ensure contextual and practical learning experiences. The results suggest that simple, targeted digital training can effectively bridge technological gaps among rural entrepreneurs, contributing to improved marketing capabilities and supporting the broader agenda of digital transformation in Indonesia’s informal sector.